Dampak Perubahan Index Inflasi pada Perhitungan Premi Excess-of-Loss Menggunakan Metode Burning Cost - Fanny Novika; Yusuf Hidayat Kalla; Elvira Yuliana (Department of Mathematics, Universitas Negeri Gorontalo, 2022)
Based on OJK data on insurance statistical documents in 2020 and 2021, the adequacy of reinsurance company premiums continued to decline throughout the year until the year 2020 a slight excess of 164.60% and 183,31% at the end of 2021. Analysis of proper premium calculation needs to be done as an effort to prevent the default from insurance companies, one of which is fire insurance with Burning Cost. The purpose of this study is to determine the impact of the inflation index that can make changes to the calculation of premiums using Burning Cost. This study uses secondary data on the value of fire insurance claims at reinsurance companies by observing historical reports of claim data from the previous year. The use of the inflation index in calculating the Excess-of-Loss premium using the Burning Cost method has a different value if it is not assumed. The more inflation index used, the higher the premium that will be charged to the ceding company.